Manufaktur dan Pengujian Burner LPG untuk Pemanasan Heater Mesin Stirling mCHPSE-012021 - Hidayat, Muhammad Arif; Al Ridho, Fatur Fadhillah; Jufrizal, Jufrizal; Supriatno, Supriatno; Nurdiana, Nurdiana (CV. IRA PUBLISHING, 2023)
This research focuses on developing a special LPG burner for the mCHPSE-012021 Stirling engine. The burner design was developed using CAD software and fabricated using machine tools and a welding process. Tests are carried out to verify how much the burner performance meets the desired specifications. The test results show that although the burner can reach the required high temperature, the thermal efficiency is still low, at 19.72%. This figure is far below the efficiency standard for household gas stoves, according to SNI 8660:2018. These findings highlight the urgency of improving burner design and efficiency to meet established standards, improving the mCHPSE-012021 Stirling engine's overall performance, and significantly increasing energy efficiency. These improvements are necessary to ensure optimal performance and efficiency in energy use in mCHPSE systems, underscoring the importance of developing more efficient and standards-compliant burner technology to support the use of Stirling engines in microenergy applications.